Difference in substrate specificity divides the yeast alkali-metal-cation/H(+) antiporters into two subfamilies - Kinclová, Olga; Potier, Serge; Sychrová, Hana (Microbiology (Reading, England), 2002)
Yeast plasma membrane Na(+)/H(+) antiporters (TC 2.A.36) share a high degree of similarity at the protein level. Expression of four antiporters (Saccharomyces cerevisiae Nha1p, Candida albicans Cnh1p, Zygosaccharomyces rouxii ZrSod2-22p and Schizosaccharomyces pombe sod2p) in a SACCH: cerevisiae mutant strain lacking both Na(+)-ATPase and Na(+)/H(+) antiporter genes made it possible to study the transport properties and contribution to cell salt tolerance of all antiporters under the same conditions. The ZrSod2-22p of the osmotolerant yeast Z. rouxii has the highest transport capacity for lithium and sodium but, like the SCHIZ: pombe sod2p, it does not recognize K(+) and Rb(+) as substrates. The SACCH: cerevisiae Nha1p and C. albicans Cnh1p have a broad substrate specificity for at least four alkali metal cations (Na(+), Li(+), K(+), Rb(+)), but their contribution to overall cell tolerance to high external concentration of toxic Na(+) and Li(+) cations seems to be lower compared to the antiporters of SCHIZ: pombe and especially Z. rouxii.
Keywords: Potassium; Cations, Monovalent; draslík; Rubidium; Saccharomyces cerevisiae; Candida albicans; lithium; rubidium; sodík; kvasinky; Lithium; kationty jednomocné; Schizosaccharomyces; Sodium; Sodium-Hydrogen Exchangers; substrátová specifita; kinetika; kovy; Substrate Specificity; Zygosaccharomyces; Metals; Yeasts; Na(+)-H(+) antiport; Kinetics